Effect of maternal haemoglobin, serum ferritin and gestational age on neonatal iron indices - Chandra Deve Varma B. S. K.; Vineela, Dantuluri; Alavilli Suma Santhi; Viyyapu Venkata Deepika (International Journal of Contemporary Pediatrics, 2023)
Background: Iron is the most common micronutrient deficiency in pregnant women and infants throughout the world, mainly in developing countries like India. 30 to 50% of the pregnancies are affected by maternal iron deficiency and in developing countries, more than 80% of the pregnant women are estimated to be anemic. The effects of perinatal iron deficiency are anemia and most importantly neurodevelopmental impairments which are long-lasting and sometimes irreversible. The main goal of this study was to determine the influence of maternal and neonatal factors on the iron stores in neonates and to estimate the appropriate time to supplement iron for neonates in different scenarios. Methods: This is a prospective observational study. Mother-infant pairs were enrolled in the study by following specific inclusion and exclusion criteria. Maternal demographic details, complications during pregnancy, intrapartum details, and neonatal details were recorded. The maternal and cord blood samples were collected for measurement of hemoglobin, serum ferritin, serum iron, total iron-binding capacity, and transferrin saturation. If failed to collect the cord blood sample, the first 24hour sample of the baby was taken into consideration in place of it. The correlation between maternal neonatal iron indices and the influence of the gestational age and IUGR on cord serum ferritin levels was analyzed by using paired t-test and chi-square test for multiple groups. A probability of p<0.05 (two-sided) was used to consider the difference as significant. Results: 125 term and 47 preterm neonates were included in the study. There was correlation between maternal and neonatal iron profiles at birth when there was severe depletion of maternal ferritin (<12µg/dl) with p values less than 0.05 for hemoglobin and serum ferritn levels. Serum ferritin levels at birth were less in preterm as compared to term neonates (mean of 128.9µg/l in the preterm vs. 156.9µg/l in the term, p=0.04). There was a significant correlation between neonatal iron indices at birth with that at 28 days of life (p<0.01). Conclusions: Neonatal iron stores are not affected unless there was severe depletion of maternal iron stores. Preterm neonates have low iron stores compared to term neonates. Gestational age is the major determinant for iron stores at birth as compared to other maternal and neonatal factors. As the most significant adverse effects of iron deficiency are irreversible and long-lasting neurodevelopmental impairments. The term and preterm babies should take prophylactic iron from eight weeks and four weeks of age respectively and continued up to the introduction of iron-fortified cereals as recommended by the American academy of paediatrics.